A critical discourse analysis of the Turkish Parliamentary vote on Iraq war in the Washington Post and the New York Times - Kilic, Zeynep Havva (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
This research is conducted to analyze the change in the language of the news texts which appeared before and after the parliamentary vote on Iraq War in 2003 at the Turkish Parliament in the American Press. Critical Discourse Analysis (CDA) method is applied to analyze twenty articles published in The Washington Post and The New York Times during the periods of February 15th, 2003- February 28th 2003 and March 1st, 2003- March 15th, 2003. The time span covers two weeks before and after the parliamentary vote. The study uses Fairclough's three-stage analysis method of CDA. In the Description stage, Halliday's framework of Systemic Functional Grammar is used to conduct mood, modality, transitivity and vocabulary analysis. Interpretation, the second stage of the analysis, establishes a link between the texts and discursive practices practice. The third stage, Explanation, explains the relationship between the interaction and social and political context. The Critical Discourse Analysis shows that before the vote, the voices of the opponents of the vote were excluded from the texts. Officials in favour of the vote were given expert positions with the ability to predict the future and warn other parties. Nevertheless, after the vote, the language was more hypothetical and the opponents were represented more often. The analysis shows that the unexpected result of the vote and its implications on the Turkish-American diplomacy of the vote played a crucial role in the changes in language of the American newspapers.